In the Antechamber of a New Global Bipolarity - Paul Dobrescu; Mălina Ciocea (Romanian Journal of European Affairs)
This paper investigates the shifts in the international balance of power, that we attribute both to the weakening status of the US globally and to the rise of regional powers. The hypothesis of the study is that the world is currently experiencing a short stage of uni-multipolarity, characterised by high instability, which is generated by the rise of new regional hegemons, the changes at the top of power hierarchies, the diminishing gap between the only superpower of the moment, the US, and the rising powers. We point to the tensions caused by a shift in power and status from the global hegemon to the regional hegemons, discussing its consequences in terms of: ideological allegiances, institutions and treaties evolution, development models legitimacy. The following decade will probably confirm the tendency for a return to a new type of bipolar order. Our analysis of the current stage of international relations reveals that we are now witnessing a double bipolarity: an American-Chinese economic bipolarity and an American-Russian military bipolarity